비만 예방을 위한 중학생 유산소능력 기준치 설정 - 이기봉(Gi Bong Lee); 이성노(Seong No Lee); 강은정(Eun Jeong Kang); 고병구(Byoung Goo Ko); 송홍선(Hong Sun Song); 박세정(Sae Jong Park); 정진욱(Jin Ug Jung) (한국체육측정평가학회지, 2015)
우리나라 청소년은 최근 신체활동의 부족으로 심폐지구력의 감소, 비만의 급증 등 건강체력요인이 급격히 악화되고 있으며 이는 청소년들의 건강을 심각하게 위협하고 있다. 이러한 인식에 따라 문화체육관광부가 2013년도 청소년기 국민체력인증 기준을 개발하였고 2015 「국민체력100 사업」에 청소년 프로그램을 추가시킴에 따라 본 연구는 청소년의 비만을 예방하기 위한 심폐지구력 기준치(cut off point)를 설정하였다. 2013년 시행된 국민체력 100사업의 청소년기 체력기준 연구참여자 중학생 2,432명을 대상으로 20m 왕복오래달리기검사 측정 결과에 대하여 정상집단과 비만집 단간의 차이분석 및 ROC 분석을 실시하였다. 이 결과에 따라 한국 중학생의 비만 예방을 위해 요구되는 성별, 연령별 최소 유산소체력 기준을 제시하였으며 체지방률, 피부두겹합, 그리고 허리둘레라는 각 비만 준거에 따라 설정된 유산소체력 기준에 대하여 타당도 및 효용성을 분석하여 제시하였다. The purpose of this study is to develop the absolute aerobic capacity evaluation standards for Korean youth established by empirical evidence in 2013 to address the minimum aerobic fitness level required to prevent obesity and to verify the validity and effectiveness. Reduction of cardiorespiratory endurance and increasing obesity in Korean youth due to the lack of recent physical activity have seriously threatened the health of the young. Accordingly, the Ministry of Culture, Sports and Tourism has developed the 2013 national youth fitness certification standard and 2015 “National Fitness Project 100”. In this study is to set the cardiorespiratory endurance thresholds (cut off point) for the prevention of obesity in adolescents. Participants were 2,432 middle school students in 2013 National Fitness Project 100. They conducted a 20m round trip run. Difference verification and receiver operating characteristic (ROC) analysis for those results were performed between the normal group and the obese group. Gender and age were required for the prevention of obesity in Korea middle school students, depending on the outcome, given the minimum aerobic fitness criterion by body fat percent, skinfolds, and waist size to analyze the validity and effectiveness of aerobic fitness for a set of standards. KCI Citation Count: 2